2021
DOI: 10.1002/pen.25756
|View full text |Cite
|
Sign up to set email alerts
|

Flow mark defects reduction of injection‐molded polypropylene by dynamically vulcanized polyolefin elastomer

Abstract: Flow mark defects (FMs) worsen surface esthetics and mechanical properties of injection‐molded polypropylene (PP). In this work, experiments and dissipative particle dynamic (DPD) simulations were used to investigate the effect of dynamically vulcanized polyolefin elastomer (POE) on FMs of injection‐molded PP. Significant FMs reduction was achieved by dynamically vulcanized POE. DPD simulations indicated that POE molecules were randomly distributed in the PP, while dynamic vulcanization led to the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…According to the coarse-grained models of beads A , B , C , D , D Me , D Et , E , and F , both Flory–Huggins parameters χ ij and interaction parameters a ij between those coarse-grained beads used in the DPD simulations were calculated according to the methods in our previous work, , as listed in Tables S2 and , respectively. Briefly, the structures of various beads were orderly performed energy minimization, geometric optimization, NPT ensemble (298 K and 1.0 bar), and NVT ensemble (298 K) calculations to reach the lowest energy configuration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the coarse-grained models of beads A , B , C , D , D Me , D Et , E , and F , both Flory–Huggins parameters χ ij and interaction parameters a ij between those coarse-grained beads used in the DPD simulations were calculated according to the methods in our previous work, , as listed in Tables S2 and , respectively. Briefly, the structures of various beads were orderly performed energy minimization, geometric optimization, NPT ensemble (298 K and 1.0 bar), and NVT ensemble (298 K) calculations to reach the lowest energy configuration.…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, the structures of various beads were orderly performed energy minimization, geometric optimization, NPT ensemble (298 K and 1.0 bar), and NVT ensemble (298 K) calculations to reach the lowest energy configuration. The subsequent DPD simulations were also carried out according to our previously published procedures. , To avoid finite-size effects, a cubic simulation box of 30 × 30 × 30 R c 3 with periodic boundary conditions was applied in all directions. In this work, it was found that the sizes and structures of aggregates/micelles had no obvious change when 400 000 simulation steps were carried out.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polypropylene (PP), one of the general-purpose plastics, is used in large quantities due to its excellent corrosion resistance, processability, and low price. [1] Due to the poor anti-impact performance of PP, especially the toughness at a low temperature, it is limited to the application of engineering plastics, especially in building materials and aerospace materials. [2][3][4] In the current stage of research, physical mixing methods are often used to improve the impact performance of PP.…”
Section: Introductionmentioning
confidence: 99%